Literature Study of Ethics and Accountability of Governance in Handling Export-based Fishery Products - Herman, ‎; Ibrahim, Akmal; Ahman, -Badu; Nara, Nurdin (KnE Social Sciences, 2025)
This study aims to examine the role of ethics and accountability in the governance of export-oriented fishery product management in Indonesia through a literature review approach. As a maritime country with one of the longest coastlines in the world, Indonesia holds significant potential in the fisheries sector, regulated through national legislation, including Law No. 31 of 2004 and its amendment, Law No. 45 of 2009. Indonesia’s fishery exports cover various categories such as fresh, frozen, canned, and processed products. Effective governance in this sector involves multiple stakeholders, with the government serving not only as a regulator but also as a facilitator, supervisor, and partner to both the private sector and local communities. These partnerships play a crucial role in ensuring efficient fish distribution and access to financing and capacitybuilding for fishermen and small-scale enterprises. The marine-based processed food industry also demonstrates promising growth, particularly through the involvement of micro, small, and medium enterprises (MSMEs). However, coastal MSMEs often face challenges related to limited capital, technical skills, and market access. This study applies the governance theory proposed by Dwiyanto and Noerhaeni, which highlights three dimensions: institutional structure, value-based decision-making, and the responsiveness of public institutions. The findings suggest that governance rooted in ethical principles and accountability can enhance transparency, effectiveness, and sustainability in managing the fisheries export sector. Strengthening cross-sectoral collaboration is essential to establish an inclusive and participatory governance system for long-term development.